PENERAPAN METODE DESIGN THINKING PADA PERANCANGAN WEBSITE UMKM KIRIHUCI - Soedewi, Sri; Mustikawan, Arry; Swasty, Wirania (Universitas Komputer Indonesia, 2022)
The rapid growth of MSMEs in West Java and the decline in consumer purchasing power due to the pandemic can cause MSME to innovate their products and carry out broader marketing/promotion strategies to survive and compete with similar businesses. MSME can use a website to increase product marketing as one of the promotional media. The advantage of a website can reach consumers widely, globally, and anyone can access it anywhere. Kirihuci is one of the SMEs from Bandung West Java, with good potential business but has not used the website as a promotional medium. The purpose of this study was to design the Kirihuci SMEs website using the Design Thinking method. The method focused on the user interface, user empathy, and user experience. Mixed-method is the research method, by conducting observations, interviews, distributing questionnaires, and searching for data literature through books or journals related to research. The results obtained in this study are the application of the Design Thinking method to the design of the Kirihuci UMKM website has provided convenience for its users. The results are from user feedback carried out at the usability testing stage regarding the appearance of the website interface design with good results.